2014
DOI: 10.1038/ncomms6841
|View full text |Cite
|
Sign up to set email alerts
|

Microwave gain medium with negative refractive index

Abstract: Artificial effective media are attractive because of the fantastic applications they may enable, such as super lensing and electromagnetic invisibility. However, the inevitable loss due to their strongly dispersive nature is one of the fundamental challenges preventing such applications from becoming a reality. In this study, we demonstrate an effective gain medium based on negative resistance, to overcompensate the loss of a conventional passive metamaterial, meanwhile keeping its original negative-index prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…For instance, a grating of wide metallic strips periodically loaded with lumped elements has been proposed to design the metasurfaces with gain for microwave cloaking [50]. In addition, subwavelength structures with a large amount of gain can be realized by using multilayered structures [48], microwave and optical metastructures with gain [71][72][73][74][75], etc. In particular, the effective gain media with pure permittivity or permeability have also been demonstrated in core-shell composites [76].…”
Section: (C)mentioning
confidence: 99%
“…For instance, a grating of wide metallic strips periodically loaded with lumped elements has been proposed to design the metasurfaces with gain for microwave cloaking [50]. In addition, subwavelength structures with a large amount of gain can be realized by using multilayered structures [48], microwave and optical metastructures with gain [71][72][73][74][75], etc. In particular, the effective gain media with pure permittivity or permeability have also been demonstrated in core-shell composites [76].…”
Section: (C)mentioning
confidence: 99%
“…The recently developed plasmon lasers showed that these dampings can be fully compensated by gain medium at the lasing state [27][28][29][30][31][32][33][34][35][36][37][38]. This intrinsic merit has great potential to enhance the performance of devices based on plasmonic resonance phenomena [39][40][41][42][43][44][45]. One example is the plasmon laser for gas phase detection where the mechanism of the sensing process relies on surface defect state modification of semiconductor material [46].…”
mentioning
confidence: 99%
“…Depending on the theoretical analysis of the SRRs proposed in [30,31], magnetic resonance is motivated by the electromotive force around the circumference of the split rings. Considering an infinite array of such SRRs arranged in three orthogonal directions with a spatial period of d and an incident magnetic field polarized along the y direction, that is, perpendicular to the SRRs, there would be an electromotive force and an induced current I along the rings, satisfying the following:…”
Section: Model and Theoretical Analysismentioning
confidence: 99%